2020
DOI: 10.1002/jmv.25755
|View full text |Cite
|
Sign up to set email alerts
|

A report of clinical diagnosis and treatment of nine cases of coronavirus disease 2019

Abstract: Coronavirus disease 2019 caused by the severe acute respiratory syndrome coronavirus 2 has become an important public health issue in the world. More than 118 000 cases were confirmed around the world. The main clinical manifestations were respiratory symptoms and occasional gastrointestinal symptoms. However, there is no unified standard for the diagnosis and treatment of COVID-19. In the retrospective analysis, we report nine cases of COVID-19, describe the history of contact, clinical manifestations, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 12 publications
(24 reference statements)
0
57
0
1
Order By: Relevance
“…A total of 15 papers that analyzed the clinical experience with the COVID-19 infection that also reported the presence of gastrointestinal symptoms, were identified. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Thirteen papers were from China, 5-13, 15-17, 19 one from Singapore, 18 and one from the World Health Organization European Region. 14 (Table 1) These papers analyzed a total of 2800 patients.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 papers that analyzed the clinical experience with the COVID-19 infection that also reported the presence of gastrointestinal symptoms, were identified. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Thirteen papers were from China, 5-13, 15-17, 19 one from Singapore, 18 and one from the World Health Organization European Region. 14 (Table 1) These papers analyzed a total of 2800 patients.…”
Section: Resultsmentioning
confidence: 99%
“…5 For further investigation, the researchers of the present study evaluated all the existing reports on treatment of COVID-19 patients, which led to finding one clinical trial 4 and 12 case-report/ case-series studies. 1,3,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] There was no mention of prescribing NSAIDs in any of these studies. This might be because of no NSAID being prescribed, which is very unlikely; or it might just be that the In this study, use of ibuprofen has been suggested for controlling the patients' fever (fever over 38.5° Celsius).…”
Section: Discussionmentioning
confidence: 99%
“…Medical staff face exhaustion, difficult triage decisions, separation from families, stigma and the pain of losing patients and colleagues, in addition to their own risks of infection. In Italy as of 3 April 2020, around 10,000 healthcare workers have been infected and 74 have died, and many others have died in countries across the globe [1,2]. While the pandemic in Africa is several weeks behind Europe and Asia, the number of cases in Africa is escalating fast [3][4][5].…”
Section: Introductionmentioning
confidence: 99%